A Comparison of Medical and Psychobehavioral Emergency Department Visits Made by Adults with Intellectual Disabilities - Yona Lunsky; Rob Balogh; Alin Khodaverdian; Deborah Elliott; Christine Jaskulski; Susan Morris (Emergency Medicine International)
Study Objective. We describe and contrast medical to psychobehavioral emergency visits made by a cohort of adults with intellectual disabilities. Methods. This was a study of 221 patients with intellectual disabilities who visited the emergency department because of a psychobehavioral or medical emergency. Patient profiles are described and logistic regression was used to assess predictors of psychobehavioral emergencies in this group, including age, residence, psychiatric diagnosis, cognitive level, and life events. Results. Ninety-eight individuals had medical emergencies and 123 individuals presented with psychobehavioral emergencies. The most common medical issue was injury and the most common psychobehavioral issue was aggression. In the multivariate analysis, life events (odds ratio (OR) 0.28; 95% confidence interval (CI) 0.10 to 0.75), psychiatric diagnosis (OR 2.35; 95% CI 1.12 to 4.95), and age group (OR 4.97; 95% CI 1.28 to 19.38) were associated with psychobehavioral emergencies. Psychobehavioral emergencies were more likely to result in admission and caregivers reported lower rates of satisfaction with these visits. Conclusion. Emergency departments would benefit from greater understanding of the different types of presentations made by adults with intellectual disabilities, given the unique presentations and outcomes associated with them.